Layilin: a multifunctional hyaluronan receptor in physiology and pathology - Jin, Chenchen; Zong, Yunfeng (Frontiers in Oncology, 2025)
Layilin (encoded by LAYN), a C-type lectin transmembrane receptor, serves as a critical molecular bridge between extracellular matrix (ECM) sensing and intracellular signaling through its interaction with cytoskeletal adaptors. Initially identified for its cytoskeletal functions, layilin has since emerged as a pleiotropic modulator of both physiological homeostasis and pathological conditions. Elevated expression of layilin is associated with poor prognosis in multiple cancers, thereby highlighting its oncogenic potential. Beyond cancer, it plays a pivotal role in rheumatoid arthritis, fibrotic progression, and chronic inflammatory diseases. This review comprehensively synthesizes the structural features, expression dynamics, and disease mechanisms of layilin, emphasizing its biological functions. Key knowledge gaps persist, particularly in understanding its spatiotemporal regulation and crosstalk with immune checkpoints. Future research should prioritize cell-type-specific mechanistic studies using advanced experimental models and the development of layilin-targeted immunotherapies. These efforts will pave the way for precise interventions in diseases driven by the dysregulation of layilin-dependent ECM signaling.